# If f(x) = ax + b

We have,

f(x) = ax + b …(i)

f(0) = 3

f(2) = 5

Replace x by 0 in equation (i), we get

f(0) = a(0) + b

3 = 0 + b [ f(0) = 3]

3 = b

b = 3

Replace x by 2 in equation (i), we get

f(2) = a(2) + b

5 = 2a + b [ f(2) = 5]

5 = 2a + 3 [ b = 3]

2a = 5 – 3

2a = 2

a = 1

Thus, a = 1 and b = 3.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

(x – 1) is a factWest Bengal Mathematics

Let us determine West Bengal Mathematics

In the polynomialWest Bengal Mathematics

Let us write the West Bengal Mathematics

If n2 West Bengal Mathematics

Both (x – 2) and West Bengal Mathematics

Let us write the West Bengal Mathematics

Let us check the West Bengal Mathematics

Let us calculate West Bengal Mathematics

Let us calculate West Bengal Mathematics